Combinatorial approach to the synthesis of substituted 1,2,4-triazines - D. N. Kozhevnikov; V. N. Kozhevnikov (Chimica Techno Acta)
This article describes a convenient and easy method of substitution of the nitrile group in 5-cyano-1,2,4-triazines with the aim of obtaining of libraries of substituted 1,2,4-triazines (about 500 compounds).